Harmonization Study Between LC‐MS/MS and Diasorin RIA for Measurement of 25‐Hydroxyvitamin D Concentrations in a Large Population Survey - Berry, Diane J. (J Clin Lab Anal, 2016)
BACKGROUND: Population‐based research on vitamin D has increased dramatically in recent years. Such studies are typically reliant on assay procedures to measure reliable and comparable levels of 25‐hydroxyvitamin D [25(OH)D] concentrations. METHODS: Concentrations of 25(OH)D(3) and 25(OH)D(2) were measured using LC‐MS/MS in 5,915 participants (aged 31 years) of Northern Finland Birth Cohort 1966. Blood samples were assayed in batches over a course of 18 months. As anomalies were present in the measurements, 200 samples were reassayed using Diasorin RIA. Agreement between measurements was assessed by Passing–Bablok regression and limits of agreement (LoA). To harmonize LC‐MS/MS with Diasorin RIA measurements, formulae were derived from the LoA. RESULTS: Concentrations measured by LC‐MS/MS were much higher than those measured by Diasorin RIA, with a mean difference of 12.9 ng/ml. Constant variation was evident between batch measurements after log transformation. Statistical formula was applied separately for each batch of LC‐MS/MS measurements, enabling us to remove both the constant and proportional bias that was evident prior to the transformation. CONCLUSION: Despite the introduction of schemes/programs to improve accuracy of assays to measure 25(OH)D, significant differences can still happen. In these instances, methods to harmonize measurements based on a relatively small number of replicates can be successfully applied to establish confidence and to enable between‐study comparisons.